Market Reaction to the Adoption of International Financial Reporting Standard in Indonesia - Sun, Yen; Steelyana, Evi; Cahyadi, Yoyo (Binus Business Review, 2014)
The aim of the study is to analyze the marketâs reaction on the adoption of International Financial Reporting Standard (IFRS) in Indonesia. Investor reaction will be perceived by the existence of abnormal return as well as the difference of trading volume. The analysis tool used is One-sample test to assess the existence of abnormal return and Paired Sample T-test to observe the difference trading volume 3 days before and after the announcement of financial report. The sample was constituted by 31 Indonesian companies randomly selected listed on LQ45 and have been impacted by the adoption of IFRS since 2011. The result shows that there is no abnormal return 3 days before and after the announcement of financial report. However, there is abnormal return on the day of announcement. Trading volume shows there is no market reaction to the IFRS adoption 3 days before and after the announcement.